1988
DOI: 10.1128/iai.56.6.1456-1463.1988
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of endocytosis of Chlamydia trachomatis by McCoy cells

Abstract: The entry of Chlamydia trachomatis into McCoy cells (fibroblasts) was studied by transmission electron microscopy. On adsorption of elementary bodies (EBs) to host cells at 37°C, the EBs were bound primarily to preexisting cell-surface microvilli. They were also observed in coated pits located at the bases of the microvilli and along smooth surfaces of the host cells and were internalized within coated vesicles at this temperature. Postembedding immunogold labeling on Lowicryl thin sections with anti-clathrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
4

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 40 publications
5
57
4
Order By: Relevance
“…EBs attach to microvillae and are rapidly endocytosed ( Fig. 1A) (Ward and Murray, 1984;Hodinka et al, 1988). At 1 h after infection, intracellular organisms still retain their condensed EB conformation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EBs attach to microvillae and are rapidly endocytosed ( Fig. 1A) (Ward and Murray, 1984;Hodinka et al, 1988). At 1 h after infection, intracellular organisms still retain their condensed EB conformation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chlamydiae are Gram-negative obligate intracellular bacteria involved in a wide spectrum of human and other vertebrate diseases. EM studies show that Chlamydia psittaci and Chlamydia trachomatis enter epithelial cells using clathrin-coated pits [55][56][57]. In these studies, the infective forms of Chlamydia, called elementary bodies, were observed at coated pits and coated vesicles, and anticlathrin immunostaining indicated the presence of clathrin at the bacterial entry sites [56].…”
Section: Other Bacteriamentioning
confidence: 97%
“…EM studies show that Chlamydia psittaci and Chlamydia trachomatis enter epithelial cells using clathrin-coated pits [55][56][57]. In these studies, the infective forms of Chlamydia, called elementary bodies, were observed at coated pits and coated vesicles, and anticlathrin immunostaining indicated the presence of clathrin at the bacterial entry sites [56]. However, EM studies of Chlamydia invasion failed to find clathrin-coated pits associated with entry of the bacterium, and monodansylcadaverine had no effect on invasion [58].…”
Section: Other Bacteriamentioning
confidence: 99%
“…C. trachomatis exists in two forms, alternating between EB (elementary body), a metabolically inactive infectious form, and RB (reticulate body), an intracellular metabolically active form. C. trachomatis EB initiates infection by attachment and internalization into host epithelial cells by mechanism yet to be identified, although receptor-mediated endocytosis has been suggested (Hodinka et al, 1988). It has been reported that C. trachomatis use GAGs (glycosaminoglycans) as adhesins to bridge with some unknown receptors for cell attachment (Zhang and Stephens, 1992;Beswick et al, 2003), but evidence for GAG-independent uptake of some C. trachomatis strains has also been documented (Taraktchoglou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that C. trachomatis use GAGs (glycosaminoglycans) as adhesins to bridge with some unknown receptors for cell attachment (Zhang and Stephens, 1992;Beswick et al, 2003), but evidence for GAG-independent uptake of some C. trachomatis strains has also been documented (Taraktchoglou et al, 2001). In addition, the formation of clathrin-coated pits for C. trachomatis internalization by host cells have been reported (Hodinka et al, 1988;Wyrick et al, 1989); however, a clathrin-independent endocytosis has been shown to occur through cholesterol-rich membrane domains (Jutras et al, 2003), suggestive of a yet unknown receptor for C. trachomatis attachment and entry.…”
Section: Introductionmentioning
confidence: 99%